Predictors of left atrial thrombus in acute ischemic stroke patients without atrial fibrillation: A single-center cross-sectional study - Cinar,Tufan (2020)
SUMMARY INTRODUCTION: The present study aimed to determine independent predictors of left atrial thrombus (LAT) in acute ischemic stroke (AIS) patients without atrial fibrillation (AF) using transesophageal echocardiography (TEE). METHODS: In this single-center, retrospective study, we enrolled 149 consecutive AIS patients. All of the patients underwent a TEE examination to detect LAT within 10 days following admission. Multivariate logistic regression analysis was performed to assess independent predictors of LAT. RESULTS: Among all cases, 14 patients (9.3%) had a diagnosis of LAT based on the TEE examination. In a multivariate analysis, elevated mean platelet volume (MPV), low left-ventricle ejection fraction (EF), creatinine, and reduced left-atrium appendix (LAA) peak emptying velocity were independent predictors of LAT. The area under the receiver operating characteristic curve analysis for MPV was 0.70 (95%CI: 0.57-0.83; p = 0.011). With the optimal cut-off value of 9.45, MPV had a sensitivity of 71.4% and a specificity of 63% to predict LAT. CONCLUSION: AIS patients with low ventricle EF and elevated MPV should undergo further TEE examination to verify the possibility of a cardio-embolic source. In addition, this research may provide novel information with respect to the applicability of MPV to predict LAT in such patients without AF.